Ethical dilemmas in the death of children - Fernandes Nunes Rangel, Alda Patrícia (O Mundo da Saúde, 2012)
The death of children is a topic that rarely figures as the focus of studies in the field of thanatology. With the increasing effort of deconstruction of the taboo of death, one sees an opportunity for further studies including parental grief (grief of parents who lose children). The aim of this study was to investigate ethical dilemmas which bereaved parents faced before the death of their children. The information was taken from a previous study of the author, who interviewed 24 bereaved parents aged from 26 to 71 years, both male and female: 18 women and 6 men, who had lost children aged from 5 to 38 years due to various causes, such as illnesses, accidents, murder and suicide. Participants were interviewed and asked to narrate what had happened from the moment of death of their children and everything else that followed the fact. It was possible to highlight information of three main themes: the ethical dilemmas caused by the circumstances of death (murder, suicide, illness and traffic accidents), dilemmas arising in the period of experiencing grief (in an amalgam of feelings, self-blame stood out) and other dilemmas regarding the quality of social support received in the bereaved setting (in some instances, extremely inappropriate ones). The content raised may provide useful information for effective interventions to be offered to bereaved parents.